Tagmemic And Syntactic Progression - Bernard Forestell (Al-Lisaniyyat)
In this article, the author attempts to show how some of the basic tenets of tagmemic theory can be applied to the search for a method which would allow us to arrive at a better understanding of syntactic progression in language teaching courses.